Neuromuscular Electrical Stimulation as Prehabilitation for Bilateral Total Knee Arthroplasty: A Pilot Within-Patient Case Series - Nita Damayanti; Whida Rahmawati; Rina Puspasari Suryana; Jeremmy Sebastian (Biology, Medicine, & Natural Product Chemistry, 2026)
Quadriceps muscle strength loss after total knee arthroplasty remains a major barrier that impairs functional recovery. Pre-operative rehabilitation has been proposed to enhance this problem, yet existing evidence is inconsistent. Neuromuscular electrical stimulation may offer a feasible option for patients limited by pre-operative pain. This pilot study explored the feasibility and observed recovery trends of a structured NMES-based prehabilitation program before the second TKA in staged bilateral cases. Seven female patients undergoing staged bilateral TKA participated in this prospective within-patient comparative case series. Each patient served as their own control. The first TKA received standard post-operative rehabilitation only, while the in-contralateral knee received a 10-week NMES prehabilitation program before the second TKA. Outcomes included pain intensity (VAS), knee range of motion (ROM), quadriceps muscle strength (MMT), and functional performance (TUG, 6 MWT) were tracked descriptively at baseline, 3,6,12 weeks and 12 months post-operative. Given the pilot nature, data are presented descriptively with individual trajectories. Results showed that from 12 months on prehabilitation knee demonstrated clinically meaningful improvements over postoperative rehabilitation, showed lower pain score, greater knee flexion ROM (112.14 vs 109.29), and quadriceps strength was higher (MMT 4.57 vs 3.57). Six of seven participants showed consistent within-trajectories favoring prehabilitation. The protocol was well-tolerated without adverse events. In this small exploratory pilot case series study, NMES-based prehabilitation before the second TKA was feasible and was associated with a more favorable recovery pattern within the same patients at 12 months. While causal conclusions cannot be made, the within-patient design helps limit inter-individual variability and support further research in larger controlled trials of prehabilitation in TKA recovery.